Immobilization of beneficial vaginal lactobacilli in polymeric nanofibers for its potential inclusion in vaginal probiotic formulations - Silva, Jessica Alejandra (2019)
Lactobacilli are the predominant microorganisms in the vaginal microbiome of healthy women. Probiotic formulations containing lactic acid bacteria (LAB) must include a high number of viable and active bacteria. The aim of this work was to evaluate the compatibility, survival and maintenance of beneficial properties of Lactobacillus gasseri CRL1320 and L. rhamnosus CRL1332 during their immobilization in polymeric nanofibers by electrospinning and after storage. The compatibility of lactobacilli with mucoadhesive polymers [polyvinylalcohol (PVA), polyvinylpyrrolidone (PVP) and chitosan/polyethylene oxide (Quit/PEO)] were evaluated. Lactobacilli were electrospunned with 15 % w/v PVA (12 kV, 0.3 mL/h, 12 cm distance to aluminum collector). The membranes were later stored at room temperature, 4 and -20 °C. Lactobacillus viability, maintenance of beneficial properties (hydrophobicity, self-aggregation and antimicrobial activity against urogenital pathogens) and nanofibers characterization was performed by SEM and FITR. The combination of PVA and PVP does not affect the bacteria viability, while Quit/PEO mixture was non-compatible. Therefore, PVA was selected for LAB immobilization. Electrospinning process was efficient since it allowed the recovery of a high number of lactobacilli (1010 UFC/g nanofiber) without modifying the surface and antimicrobial properties of the two strains. Lactobacillus immobilized in nanofibers were evidenced by SEM and FTIR. A higher survival rate was obtained in L. rhamnosus CRL1332 than in L. gasseri CRL1320 after the immobilization. The highest viable cells were kept in nanofibers stored at -20 °C. However, a decrease of viable cells (lower than 1 x 107 CFU/g) was observed in L. gasseri CRL1320 and L. rhamnosus CRL1332 at 28 and 56 days, respectively. The results obtained support the inclusion of lactobacilli into polymeric nanofibers for the design of vaginal formula. However, further studies are being carried out to improve the Lactobacillus survival.